2016
DOI: 10.1037/pas0000223
|View full text |Cite
|
Sign up to set email alerts
|

Assessing trauma and posttraumatic stress disorder: Single, open-ended question versus list-based inventory.

Abstract: Trauma exposure is a precursor to a diagnosis of posttraumatic stress disorder (PTSD). A dearth of empirical evidence exists on the impact of different measurement practices on estimates of trauma exposure and PTSD within representative epidemiological samples. In the present study, we examined differences in reported trauma exposure and rates of PTSD using single, open-ended question versus list-based trauma assessments in a general community sample. Using data from the third wave of the Montreal epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Asking more open questions about trauma exposure, such as “What traumatic events have happened to you?” (Crosby, , p. 522), could be an effective way to begin screening for diverse traumatic life events. However, other researchers have advocated for using comprehensive multi‐item trauma exposure assessments because they found that single, open‐ended questions resulted in underestimation of trauma exposure among women (Monson, Lonergan, Caron, & Brunet, ). Future research should work towards determining best practices for comprehensive trauma history screening.…”
Section: Discussionmentioning
confidence: 99%
“…Asking more open questions about trauma exposure, such as “What traumatic events have happened to you?” (Crosby, , p. 522), could be an effective way to begin screening for diverse traumatic life events. However, other researchers have advocated for using comprehensive multi‐item trauma exposure assessments because they found that single, open‐ended questions resulted in underestimation of trauma exposure among women (Monson, Lonergan, Caron, & Brunet, ). Future research should work towards determining best practices for comprehensive trauma history screening.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of our measurement of PTSD was that we did not limit it to a single item, which yields lower prevalence estimates than a list-based assessment (e.g., Monson, Lonergan, Caron, & Brunet, 2016). However, we could not determine whether the exposure met the PTSD diagnostic criterion that requires the stressor to relate to actual or threatened death, serious injury, or sexual violation, and so we are unable to determine whether the extent of PTSD symptomatology accurately reflects the prevalence of PTSD among psychiatric hospital workers in this study.…”
Section: Limitations and Implications For Researchmentioning
confidence: 99%
“…The authors of the LSC‐R recognized sex‐based disparities in trauma exposure, and developed the LSC‐R for use with women, beginning with focus group discussions with older women to learn about trauma across the lifespan to inform the content of the instrument (McHugo et al., ). A recent study found using a single, open‐ended question resulted in underestimation of trauma exposure among women, as compared to a comprehensive multi‐item assessment (Monson, Lonergan, Caron, & Brunet, ).…”
Section: Methodsmentioning
confidence: 99%